O uso de cartas terapêuticas em psicoterapia de grupo - Barros, Ludoana Pousa Corrêa de Paiva Rocha (2010)
The use of written communication in the clinical practice has been reported since the 1940 decade. However, it is only in the narrative therapy domain that the term therapeutic letters and its practice aimed towards intervention gain identity. These letters, differently from social letters, has context, content, intentions and effects caused on the patient and the therapist as the focus. They are more literal then diagnoses letters, exposing situations and possibilities more than explaining something. They document history, report present developments and future forecasts. From this context, the objective of this project is to investigate the meanings of therapeutic letters in psychotherapeutic groups that use this resource, specifically in relation to its written process, considering the logic that organizes its writing and the therapeutic principles used to attend specific functions. To achieve this project´s objective 12 closed character group meetings took place, with the attendance of a field therapist and two therapists that formed a reflexive team. This group was composed by 9 people, of both sexes, with ages varying from 31 to 52 years. The letters were written by the field therapist after the group sessions, and handed to the participants in the beginning of the following session. From the analysis carried out in one of the letters written by the therapist, I notice that the letters have various principles and procedures of language useful for the construction of preferred narratives, being an important document in the re-authoring process. I highlight amongst these principles: the deconstructing the subjugated self, the searching for exceptions, the maintaining a not-knowing position and the internalizing personal agency. From the process of writing the letter, the therapist uses procedures relative to each one of these principles, adding to other resources and linguistic strategies to promote determinate therapeutic objectives. This way, recognizing knowledge as a socially constructed discursive practice, the concepts and questions here presented seek to offer other possibilities of reflection and conversation, craving the expansion of available speeches relative to the issue of the letters in the therapeutic context.